Label‐free deep shotgun proteomics reveals protein dynamics during tomato fruit tissues development. (22nd March 2017) - Szymanski, Jedrzej; Levin, Yishai; Savidor, Alon; Breitel, Dario; Chappell‐Maor, Louise; Heinig, Uwe; Töpfer, Nadine; Aharoni, Asaph
Summary: Current innovations in mass‐spectrometry‐based technologies allow deep coverage of protein expression. Despite its immense value and in contrast to transcriptomics, only a handful of studies in crop plants engaged with global proteome assays. Here, we present large‐scale shotgun proteomics profiling of tomato fruit across two key tissues and five developmental stages. A total of 7738 individual protein groups were identified and reliably measured at least in one of the analyzed tissues or stages. The depth of our assay enabled identification of 61 differentially expressed transcription factors, including renowned ripening‐related regulators and elements of ethylene signaling. Significantly, we measured proteins involved in 83% of all predicted enzymatic reactions in the tomato metabolic network. Hence, proteins representing almost the complete set of reactions in major metabolic pathways were identified, including the cytosolic and plastidic isoprenoid and the phenylpropanoid pathways. Furthermore, the data allowed us to discern between protein isoforms according to expression patterns, which is most significant in light of the weak transcript‐protein expression correspondence. Finally, visualization of changes in protein abundance associated with a particular process provided us with a unique view of skin and flesh tissues in developing fruit. This study adds a new dimension to the existing genomic, transcriptomic and metabolomic resources. It is therefore likely to promote translational and post‐translational research in tomato and additional species, which is presently focused on transcription. Significance Statement: Proteomics allows quantitative profiling of individual proteins and assessment of post‐translational modifications, subcellular localization, and dynamics of protein‐protein interactions. Here we used cutting edge mass spectrometry‐based technology to generate an extensive proteomics dataset for tomato fruit flesh and skin, which will facilitate identification of metabolic mechanisms associated with tomato fruit quality traits.